Study of overloading retardation on fatigue crack propagation behavior in 300M steel. Issue 11 (22nd August 2022) - Zhou, Song; Shen, Zhen Xin; Wang, Lei; An, Jinlan
Abstract: Based on the fatigue life change of 300M landing gear steel due to overload during service, this study innovatively designed four overload modes according to the actual load spectrum of the landing gear. In this study, the application of overload continued until the specimen failed, and the effects of overload ratio, overload type and specimen thickness on the crack propagation behavior of 300M steel were compared and analyzed. The fatigue crack growth rate and fracture morphology of the specimens were characterized and analyzed, and the influence mechanism of the crack growth rate at each stage under different types of overload conditions and the influence of the thickness of the specimen on the overload delay effect were discussed.